TRUE POLAR WANDER AND SUPERCONTINENTS - Evans D.A.D. (My University, 2003)
I present a general model for true polar wander (TPW), in the context of supercontinents and simple modes of mantle convection. Old, mantle-stationary supercontinents shield their underlying mesosphere from the cooling effects of subduction, and an axis of mantle upwelling is established that is complementary to the downwelling girdle of subduction zones encircling the old supercontinent. The upwelling axis is driven to the equator by TPW, and the old supercontinent fragments at the equator. The prolate axis of upwelling persists as the continental fragments disperse; it is rotationally unstable and can lead to TPW of a different flavor, involving extremely rapid (≤m/year) rotations or changes in paleolatitude for the continental fragments as they reassemble into a new supercontinent. Only after several hundred million years, when the new supercontinent has aged sufficiently, will the downwelling zone over which it amalgamated be transformed into a new upwelling zone, through the mesospheric shielding process described above. The cycle is then repeated.
Keywords: True polar wander; Supercontinents; Equator